Comparison of the low-frequency predictions of Biot's and de Boer's poroelasticity theories with Gassmann's equation - Gurevich, Boris (American Institute of Physics, 2007)
Predictions of Biot's theory (BT) of poroelasticity (J. Acoust. Soc. Am. 28, 168 (1956)) and de Boer's theory of porous media (TPM) (Theory of Porous Media (Springer, Berlin, 2000)) for the low-frequency bulk modulus of a fluid-saturated porous medium are compared with the Gassmann equation (Vierteljahrsschr. Naturforsch. Ges. Zur. 96, 1 (1951)). It is shown that BT is consistent with the Gassmann equation, whereas TPM is not. It is further shown that the bulk modulus of a suspension of solid particles in a fluid as predicted by TPM is only correct if the particles are incompressible.